Mathematical modeling of phenomena of dynamic recrystallization during hot plastic deformation in high-carbon bainitic steel - T. Dembiczak; M. Knapinski; B. Garbarz (Metalurgija, 2017)
Based on the research results, coefficients were determined in constitutive equations, describing the kinetics of dynamic recrystallization in high-carbon bainitic steel during hot deformation. The developed mathematical model takes into account the dependence of changing kinetics in the size evolution of the initial austenite grains, the value of strain, strain rate, temperature and time. Physical simulations were carried out on rectangular specimens measuring 10 × 15 × 20 mm. Compression tests with a plane state of deformation were carried out using a Gleeble 3800.